Determination of bacterial contamination of flies (Musca Domestica) in different environments at Joybar city - Fatemeh Jafari; فرزاد متولی حقی; Masoumeh Eslamifar; Mahmoud Fazeli Dinan; Ali Jafari (Pizhūhish dar Bihdāsht-i Muḥīṭ., 2019)
Abstract Background and Aim: House flies are able to transmit pathogenic organisms from infected materials to human. The role of the flies in the transmission of many diseases has been demonstrated. This study was conducted to determine the bacterial contamination of M.domestica flies in various sources of Joybar city.   Materials and Methods: A total of 384 household flies were collected from five sources including urban and rural solid wastes, hospital campus, coastal areas and slaughterhouses. Samples were transferred to the microbiology laboratory of the school of public health in some sterilized glass containers, and standard tests were carried out to isolate and identify bacterial species.   Results: Escherichia coli was the dominant species in the samples. From all of the samples, 46% E.coli, 19% Staphylococcus aureus, 9.98% Staphylococcus epidermidis and 16.66% Enterobacter Aerogenus were isolated.   Conclusion: The results of this study confirmed that the presence of these insects in the public places and different parts of the environment is regarded as a disturbing agent, and vector of pathogens. Since public spaces should not be a source of contamination,  the implementation of the sanitation programs and control of these insects seems to be so necessary to create a safe and healthy environment.